Representation of Gender Binarism in Frida Kahlo's "Self Portrait with Stalin" - Shajwan N. Fatah; Ala B. Ahmed (Engiscience Publisher, 2023)
Frida Kahlo's "Self Portrait with Stalin" 1954, has been related to biographical, cultural, and national references. It is examined as an allegory of the artist's troubled personal relationships with political figures; her antagonism towards the Soviet Union leader, Joseph Stalin, her af-fair with the Marxist revolutionary, Leon Trotsky, who was later assassinated by Stalin, and her involvement in the communist party. Moreover, critics have shed light on Kahlo's factual references, such as her Tehuana dress which is seen as an appreciation for her Mexican herit-age and also as a disguise for her physical problems. In this paper, we try to disregard these conventions, instead, we focus on several hidden premises in the painting such as power rela-tions (Michel Foucault) and gender problems (Helene Cixous). These concepts are explored through the semiotic reading of the details including the composition, texture, and elements of the art artwork.